Helicobacter pylori Outer Membrane Vesicles Protect the Pathogen From Reactive Oxygen Species of the Respiratory Burst - Lekmeechai, Sujinna; Su, Yu-Ching; Brant, Marta; Alvarado-Kristensson, Maria; Vallström, Anna; Obi, Ikenna; Arnqvist, Anna; Riesbeck, Kristian (Frontiers in Microbiology, 2018)
Outer membrane vesicles (OMVs) play an important role in the persistence of Helicobacter pylori infection. Helicobacter OMVs carry a plethora of virulence factors, including catalase (KatA), an antioxidant enzyme that counteracts the host respiratory burst. We found KatA to be enriched and surface-associated in OMVs compared to bacterial cells. This conferred OMV-dependent KatA activity resulting in neutralization of H2O2 and NaClO, and rescue of surrounding bacteria from oxidative damage. The antioxidant activity of OMVs was abolished by deletion of KatA. In conclusion, enrichment of antioxidative KatA in OMVs is highly important for efficient immune evasion.